Partisipasi Masyarakat Dalam Penyusunan Rencana Kerja Pemerintah Daerah (RKPD) Di Kota Palu: Partisipasi Masyarakat Dalam Penyusunan Rencana Kerja Pemerintah Daerah (RKPD) Di Kota Palu - hidayatullah, feby kalsum; Kurnia, Intam; Ferianto, Fiki (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
ABSTRACT Preparation of the Regional Government Work Plan (RKPD) of Palu City. The research method used is Descriptive Qualitative, which provides a description of the phenomenon or focus of the problem being studied that occurs at the research location according to existing facts. The data collection techniques used are observation, in-depth informant interviews and documentation to collect the required data in the form of primary and secondary data. The theories used in this research are the dimension theory by Dietz & Stern and the ladder theory of participation by Arnstein. The results showed that the level of Publik Participation in the Preparation of the Regional Government Work Plan (RKPD) of Palu City. Is in the Non Participation category. This can be seen in the musrenbang process carried out at each level where the community is involved but the musrenbang forum itself is only a forum for legalizing the government's agenda where the community has no room to determine because in the end the decision is taken by the government itself. And in the Therapy ladder, at this level there is already communication but it is still very limited. Communication is more emphasized in one direction, namely top down. In the Therapy ladder, it is described as hearing activities from the community, however, it does not have any influence on policies or programs that have taken place. The community does not have the space and capacity to contribute to decision-making. Keywords: Policy Formulation, Publik Participation, RKPD